Impact of war on the environment: ecocide - Yohannes Desalegn Wirtu; Umer Abdela (Frontiers in Environmental Science)
This paper reviews the militaristic consequences on Mother Earth and in particular ecocide or the mass degradation of the biological forms in regards to war. Wars are recorded from the ancient Egyptian dynasty to the modern era, and all are left concerning effects on mother nature such as deforestation, loss of biodiversity, soil erosion, and water, and air pollution. Some conflicts that are especially noted are the Vietnam War, Gulf War, and contemporary wars in Ukraine which are considered as examples of ecocide in today’s context. To provide a clearer understanding of our methodology, we employed a comprehensive literature review approach. This involved systematically analyzing existing studies that document the environmental impacts of warfare across various historical and contemporary conflicts. We categorized the findings based on specific environmental consequences, such as deforestation, biodiversity loss, and pollution. Additionally, we incorporated case studies from significant wars to illustrate patterns of ecocide. The paper looks at how environmental hazard is performed through wars such as direct environmental destructive activities like bombings migration of populations and their needs and socio-economic pursuits. Legal instruments especially those at the international level and international environmental law concerning ecocide as a developing crime are also examined for the problem of ecological injustice. Finally, the review looks at rehabilitation and reconstruction measures including community-based efforts like reforestation and the restoration of ecosystems. The paper finally ends by advocating the threats of international ecocide by calling for international cooperation and treaties on ecocide and no environmental degradation in post-war countries.